Gambaran Kasus Difteri di Provinsi DKI Jakarta Tahun 2015-17 Desember 2017 - Oktaviannoor, Husda; Djuwita, Ratna (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Diphtheria is a contagious disease whose transmission is very fast and can cause death especially in children. In 2017 it was reported, there were 11 provinces in Indonesia experiencing diphtheria outbreaks, one of which is DKI Jakarta Province. This study aims to see an overview of diphtheria cases in DKI Jakarta in 2015 - December 17, 2017.Methods: This research is a descriptive study with a case report design. The sample in this study amounted to 59 cases. The implementation was carried out on 25 to 29 December 2017.Result: DKI Jakarta Province reported 7 diphtheria cases in 2015, 14 new cases in 2016 and 38 cases in January to 17 December 2017. Where the highest cases were in East Jakarta with the number of 18 cases from 2015 – December 17, 2017. And the number of diphtheria cases is more common in men, especially in children aged 0 - 9 years. In the 46th week of 2017 was the peak report on the incidence of diphtheria as many as 12 new cases in 1 week so that DKI Jakarta Province was declared to have an outbreak of diphtheria.Conclusion : Cases of diphtheria in DKI Jakarta from 2015 - December 17, 2017 continue to increase so special efforts are needed to prevent transmission of this disease.